The Holy Spirit in the New Testament - Carroll, John T. 1954- (Nashville Abingdon Press, 2018)
"That's the Spirit!": a Spirited introduction to the book -- The Spirit in Jewish scripture -- The Spirit in Second Temple literature and Greco-Roman culture -- The Holy Spirit in Mark and Matthew -- The Holy Spirt in Luke-Acts -- The Spirit-paraclete in the gospel of John and First John -- The Holy Spirit in the letters of Paul -- The Holy Spirit in First Peter, Hebrews, and Revelation -- Trajectories and themes: theological dimensions of the Spirit in the New Testament.
Includes bibliographical references and indexes
Keywords: Bible -- Theology; Bible -- Criticism, interpretation, etc; Holy Spirit (Judaism); Holy Spirit -- Biblical teaching